1991
DOI: 10.1055/s-0038-1646393
|View full text |Cite
|
Sign up to set email alerts
|

Variable Effects of Radiological Contrast Media on Thrombus Growth in a Rabbit Jugular Vein Thrombosis Model

Abstract: SummaryWe studied the effect of an ionic high osmolar contrast medium (Ioxitalamate), an ionic low osmolar contrast medium (Ioxaglate) and various nonionic low osmolar contrast media (Iopamidol, Iopromide and Iohexol) on thrombus growth in a rabbit jugular vein thrombosis model. Thrombus growth was determined by the accretion of 125I-labeled fibrinogen onto autologous preformed thrombi in rabbit jugular veins at various time-intervals from 15 min up to 10 h after infusion of the study solution.The ionic low os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Nevertheless, several lines of evidence suggest that true differences in thrombotic risk exist between contrast agents. Using a rabbit jugular vein thrombosis model, Levi et al demonstrated that ionic contrast agents were associated with less thrombus growth than nonionic contrast agents (27). In this study, % thrombus growth in 3 h was approximately 15% and 35% in animals receiving ioxaglate (low osmolar ionic) and ioxithalamate (high osmolar ionic), respectively, compared to approximately 100% in animals receiving the nonionic agent, iopamidol.…”
Section: Discussionmentioning
confidence: 52%
“…Nevertheless, several lines of evidence suggest that true differences in thrombotic risk exist between contrast agents. Using a rabbit jugular vein thrombosis model, Levi et al demonstrated that ionic contrast agents were associated with less thrombus growth than nonionic contrast agents (27). In this study, % thrombus growth in 3 h was approximately 15% and 35% in animals receiving ioxaglate (low osmolar ionic) and ioxithalamate (high osmolar ionic), respectively, compared to approximately 100% in animals receiving the nonionic agent, iopamidol.…”
Section: Discussionmentioning
confidence: 52%
“…In a rabbit jugular vein thrombosis model, the injection of a non-ionic CM surprisingly provoked an increase in thrombus growth in comparison to the saline control. Significant inhibition of thrombus growth was observed with ionic CM [31]. In a canine model of arterial injury resulting from balloon dilatation.…”
Section: Experimental Thrombosis Modelsmentioning
confidence: 93%
“…Other studies have failed to demonstrate an increased inci dence of thrombosis during venography [421 or changes in plasminogen or antiplasmin lev els [43] when iohexol was used as the contrast agent. Although there are no previous studies of the effects of iothalamate on clot structure, investigations of other high osmolar, ionic contrast agents, such as diatrizoate [5,43] and ioxitalamate [2] have demonstrated inhibi tion of fibrin polymerization [5], inhibition of thrombus growth [2] and inhibition of platelet aggregation [5], The preservation of force development at concentrations of iohexol adequate to inhibit collagen-induced aggregation is intriguing. Collagen is an indirect agonist of platelet ag gregation.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographie contrast media have been re ported to alter coagulation, fibrinolysis and platelet function [1], Ionic agents have sig nificant anticoagulant effects [2]. Nonionic agents have less anticoagulant properties, and coronary artery thromboembolic events have been reported in association with their use [3,4].…”
Section: Introductionmentioning
confidence: 99%